Assessing the risk of adverse pregnancy outcomes and birth defects reporting in women exposed to ganciclovir or valganciclovir during pregnancy: a pharmacovigilance study. (25th March 2023) - Contejean, Adrien; Leruez-Ville, Marianne; Treluyer, Jean-Marc; Tsatsaris, Vassilis; Ville, Yves; Charlier, Caroline; Chouchana, Laurent
Abstract: Objectives: Cytomegalovirus (CMV) is the leading cause of congenital infection worldwide. Reference anti-CMV treatment is valganciclovir/ganciclovir, which is contraindicated in pregnancy given questions about teratogenicity. Methods: We analysed reports from VigiBase, the world's largest safety database, and performed a disproportionality analysis of adverse pregnancy outcomes associated with (val)ganciclovir compared with any other drugs or with (val)aciclovir as comparators. Results: Among 3 104 984 reports related to childbearing-age women or to pregnancy topics, 6186 were exposed to (val)ganciclovir or (val)aciclovir including 251 adverse pregnancy outcomes with (val)ganciclovir ( n  = 34) or (val)aciclovir ( n  = 217). We did not evidence any increased reporting of any adverse pregnancy outcome [miscarriage, stillbirth, small weight for gestational age, preterm birth (<37 weeks of gestation)] or birth defects with (val)ganciclovir compared with the use of (val)aciclovir during pregnancy. Four cases of oesophageal and anorectal atresia were identified with (val)ganciclovir, which may be related to concomitant drugs/medical conditions and require further analyses. Conclusions: These preliminary results require confirmation but suggest the possibility for trial evaluation of val(ganciclovir) in severe maternal or fetal CMV infections.